A Theoretical Model Of Poverty Approach Within The Framework Of Fiscal Decentralization, Minimum Wages, And Government Accountability - Maharajabdinul, Maharajabdinul; Mahaputra, Mahaputra (Program Pascasarjana STIE Amkop Makassar, 2023)
The purpose of this paper is to provide a model for poverty alleviation by looking at maximizing the utility of social planners by adopting fiscal decentralization, minimum wages and quality of government, which then combines three models that lead to the utility function of social planners that see pro-poor regional and central government spending, absorption of labor faced by a minimum wage, and achieving minimum growth in an accountable government. Keywords: Poverty Model, Poverty; Decentralization, Quality of Local Government, UMP; Poverty.